2019
DOI: 10.1186/s12891-019-2442-2
|View full text |Cite
|
Sign up to set email alerts
|

Two stage revision with a proximal femur replacement

Abstract: BackgroundDespite very good prosthesis retention times, the growing numbers of primary implantations of hip endoprostheses are leading to increasing numbers of revision operations. Periprosthetic infection, particularly in revision implants, often leads to a massive loss of bone stock, so that in a two-stage exchange the only option left is implantation of a megaendoprosthesis. This retrospective study investigated the clinical and functional outcome for patients who received megaendoprostheses in the proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Following elimination of duplicate articles, predetermined inclusion and exclusion criteria were applied. In total, 18 articles met the inclusion criteria and were included in the final analysis [ 3 , 4 , 17 32 ] (Table 1 ). Consensus on which articles would be analyzed in the present study was achieved by discussion between the reviewers based on the predetermined inclusion and exclusion criteria described above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following elimination of duplicate articles, predetermined inclusion and exclusion criteria were applied. In total, 18 articles met the inclusion criteria and were included in the final analysis [ 3 , 4 , 17 32 ] (Table 1 ). Consensus on which articles would be analyzed in the present study was achieved by discussion between the reviewers based on the predetermined inclusion and exclusion criteria described above.…”
Section: Resultsmentioning
confidence: 99%
“…All eighteen studies specified the indication, at time of surgery, for use of the PFR, however three cases were not clearly specified (0.5%) [ 3 , 4 , 17 32 ]. Among the studies where details were reported (629 hips), PFRs were most commonly used in revision THA for the treatment of periprosthetic fractures (187 hips, 29.7%), followed by 2-stage revisions with severe bone loss for PJI (184 hips, 29.3%), and aseptic loosening (AL) of previously implanted THA (163 hips, 25.9%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important benefit of antibiotic-impregnated cement is its ability to provide a high concentration of antibiotics at the local site [11]. Antibiotic-impregnated cement is a treatment option for osteomyelitis and periprosthetic infections [2].…”
Section: Discussionmentioning
confidence: 99%